Effective removal of anionic and cationic dyes by kaolinite and TiO2/kaolinite composites. (2nd January 2018) - Hajjaji, W.; Andrejkovičová, S.; Pullar, R.C.; Tobaldi, D.M.; Lopez-Galindo, A.; Jammousi, F.; Rocha, F.; Labrincha, J.A.
Abstract: The present study investigated the removal of methylene blue (MB) and orange II (OII) dyes from synthetic wastewater by means of adsorption and photocatalysis using natural kaolins. ForMB adsorption, the raw kaolinite-rich samples showed the greatest adsorption capacity, with rapid uptake (90% after 20 min). The experimental results were fitted better using the Langmuir isotherm model parameters compared to the Freundlich model, suggesting that the adsorption corresponds to monolayer coverage of MB molecules over the kaolinite surface. For OII, neither the Langmuir nor the Freundlich model gave reliable results, because the adsorption of anionic dye molecules by the clayey particles is not favoured. Mixtures of kaolinite/Degussa TiO2 were also prepared, and their photocatalytic properties under UVlight exposure were investigated. Decolourization of MB solutions was observed, even in a mixture with low TiO2 content. This is related to the combined effect of adsorption and photocatalysis and, unlike the pure clay samples, the efficiency of such mixtures against OII was only slightly weaker (80–94%). For TiO2-impregnated clays, with the kaolinite layers separated by sol-gel TiO2 particles, the MB removal was slow and effective only after >24 h due to the complexity of the bonding of MB molecules. On the other hand, the removal performance against OII solutions was very efficient (nearly 100%) within only 2 h. This excellent performance was attributed to morphological changes in clay particles.